2020
DOI: 10.1039/d0cp04377j
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of interacting magnetic nanoparticles: effective behavior from competition between Brownian and Néel relaxation

Abstract: The intriguing properties of magnetic nanoparticles have sparked a growing number of theoretical studies as well as practical applications. Here, we provide the first comprehensive study of the influence of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 43 publications
3
56
0
Order By: Relevance
“…Another reason could be that MNPs form clusters of a few particles in the experimental setting, which Dennis et al consistently found for nanomag-D SPIO from small-angle neutron scattering (SANS) and transmission electron microscopy [ 37 ]. Clustering of MNPs has been suggested to lead to increased particle–particle interaction, changed effective anisotropy, and restriction of MNP rotatability [ 38 , 39 , 40 ]. Although the interplay of these clustering effects on MNP relaxation behavior is the subject of ongoing discussions [ 39 , 40 , 41 , 42 ], it is overall assumed to diminish the experimental signal intensity [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason could be that MNPs form clusters of a few particles in the experimental setting, which Dennis et al consistently found for nanomag-D SPIO from small-angle neutron scattering (SANS) and transmission electron microscopy [ 37 ]. Clustering of MNPs has been suggested to lead to increased particle–particle interaction, changed effective anisotropy, and restriction of MNP rotatability [ 38 , 39 , 40 ]. Although the interplay of these clustering effects on MNP relaxation behavior is the subject of ongoing discussions [ 39 , 40 , 41 , 42 ], it is overall assumed to diminish the experimental signal intensity [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clustering of MNPs has been suggested to lead to increased particle–particle interaction, changed effective anisotropy, and restriction of MNP rotatability [ 38 , 39 , 40 ]. Although the interplay of these clustering effects on MNP relaxation behavior is the subject of ongoing discussions [ 39 , 40 , 41 , 42 ], it is overall assumed to diminish the experimental signal intensity [ 43 ]. Both the rise of particle–particle interaction—although purposefully excluded from this study—and the influence of varying could be investigated in future MC-simulations studies (e.g., by diffusion-limited colloidal aggregation [ 42 ]) to advance the understanding of its influence on mixed frequency excitation signal generation.…”
Section: Discussionmentioning
confidence: 99%
“…SAR value can be defined by absorbed/converted magnetic energy into thermal energy [Fortin, 2008]. Brownian relaxation is mainly effective for magnetic nanoparticles suspended in a viscous liquid, which permit the nanoparticles rotate freely [Ilg, 2020]. On the other hand, Neel relaxation occurs by Eddy currents on the particle surface [Hergt, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…The magneto heating originating from two basic mechanisms, which govern the magnetization relaxation of magnetic nanoparticles. The internal magnetization relaxation and the rotational diffusion of whole magnetic nanoparticles are defined Néel relaxation and Brownian relaxation, respectivley [Ilg, 2020]. The mechanism of magneto-heating is expected to be mainly depended on both mechanisms of Neel relaxation and Brownian relaxation [Celik, 2014;Ilg, 2020].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation